STRATEGI KEWIRAUSAHAAN KEDAI KOPI DI KOTA MANADO DALAM MEMBANGUN LOYALITAS PELANGGAN : STUDI KUALITATIF PADA PENGALAMAN PELANGGAN - Lidya Djuwita Pratiwi Canon; Injilia Wulan Gratia Wua; Fitayantri Tamau (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines how coffee shop entrepreneurs in Manado build customer loyalty through entrepreneurial strategies reflected in customer experience. Using a qualitative multiple-case study design, data were collected from selected local coffee shops in Manado through semi-structured interviews with owners/managers, key staff, and loyal customers, complemented by on-site observations and document reviews (menus, promotions, social media content, and online reviews). The analysis employed thematic coding to identify recurring patterns linking entrepreneurial decisions—such as product and service innovation, atmosphere-based differentiation, pricing and bundling, digital marketing practices, and community engagement—to key dimensions of customer experience (product consistency, service interaction, comfort, perceived value, and social ambience). The findings indicate that loyalty is primarily strengthened when value propositions are consistently delivered across daily operations, supported by responsive service and credible digital presence. Community-based activities and collaborations further enhance emotional attachment and word-of-mouth, while operational inconsistency and overreliance on key personnel weaken repeat visits. This research contributes to entrepreneurship and service management literature by contextualizing loyalty formation in an urban local-coffee-shop setting and offers practical insights for small business owners to design experience-driven strategies that sustain repeat patronage.